(untitled) (Research, Society and Development, 2025)
Objective: To understand current scientific knowledge about the main motivators and barriers that influence university students in the decision to donate blood. Introduction: Although blood donation is essential for public health, donation rates often do not meet the necessary demand. College students are a potential group for donation campaigns because they are young and healthy. Understanding the factors that influence this population to donate blood can contribute to more effective blood collection and retention strategies. The research question that will guide the inclusion of studies was constructed by the PCC strategy, where P- population (students), C-concept (factors that influence blood donation) and C-context (higher education environments) : “What are the barriers and motivations for donating blood among students in higher education settings?” Methods: An integrative literature review will be conducted. Database research will be done in the Virtual Health Library (BVS), in the Scientific Electronic Library Online (Scielo) and in PubMed, as these are the databases with the highest indexing of health journals. Results: Results will be interpreted in light of the literature review and discussed in relation to existing theories on blood donation behavior and health communication. Based on the methodological procedures described, it is expected to obtain a series of results, products or processes that contribute to the advancement of knowledge on the subject, which could encourage the development of effective strategies to promote blood donation in this specific demographic group.